2003
DOI: 10.1053/rapm.2003.50039
|View full text |Cite
|
Sign up to set email alerts
|

Continuous lumbar plexus block: Use of radiography to determine catheter tip location

Abstract: Epidural spread of local anesthetic during lumbar plexus block should be expected to be relatively common. It can be easily identified clinically with fractionated doses of local anesthetic. The catheter tip was identified in the epidural space by radiographic verification in only 1.8% of cases. This expensive procedure is therefore unnecessary except when an unusual location is suspected, but not necessary to confirm a catheter assumed to be correctly positioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…This misplacement may be more likely with the more medial approach described by Pandin et al [6], used in the present surgeries, than by the approach described by Chayen et al [7]. In the method of Pandin et al, the puncture site is located 3 cm lateral to the interspinous line, 1 to 2 cm medial to the approach described by Chayen et al In addition, in our case 2, the needle may have been advanced too far after contact with the transverse process of the lumbar vertebra (3 cm); 2 cm is advocated to prevent misplacement [3].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This misplacement may be more likely with the more medial approach described by Pandin et al [6], used in the present surgeries, than by the approach described by Chayen et al [7]. In the method of Pandin et al, the puncture site is located 3 cm lateral to the interspinous line, 1 to 2 cm medial to the approach described by Chayen et al In addition, in our case 2, the needle may have been advanced too far after contact with the transverse process of the lumbar vertebra (3 cm); 2 cm is advocated to prevent misplacement [3].…”
Section: Discussionmentioning
confidence: 74%
“…Inadvertent central neuraxial block is a well-described complication of the posterior approach to lumbar plexus block [2][3][4][5]. Although this type of complication is relatively rare, inadvertent epidural or spinal injections of large volumes of local anesthetic may be detrimental, especially in patients who have critical comorbidities (which provide the indication for the peripheral block in the fi rst place).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this could be a multifactorial complication related to factors such as the position of the needle before the injection, unintended injection close to the intervertebral foramen, administration of larger volumes of LA and the presence of spinal deformity. 38 …”
Section: Discussionmentioning
confidence: 99%
“…8. Schematic structure of the nerve fibre Studies using MRI [Davidson EM et al, 2009], CT (See Figure 9), epiduroscopy, marked radioactive isotopes [De Biasi P et al, 2003] and studies on cadavers have demonstrated the existence of a vertical conjunctive septum and of horizontal septa which practically divide the epidural space [Aggarwal A et al, 2009]. These septa prevent the substance from diffusing amongst them, probably determining the asymmetry of the block.…”
Section: Pcea Vs Ceimentioning
confidence: 99%